Products and assistive technologies in the information society: Analysis and cataloging from a university reference center for the inclusion of disabled people (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
This research presents a qualitative and descriptive study on the resources of the C.A.R.D. CAPACITAS-UCV, whose mission is to promote the personal autonomy ofdisabled people, by enabling adapted environments through the use of personalizedSupport Products (AP). Given the large number and variety of APs for access toInformation and Communication Technologies (ICT), the existence of this type ofreference centers is necessary to serve as a point of support and advice. The studyhighlights the needs covered by the centers and the importance of having a reference catalog of AP for access to ICT, for the improvement of the quality of life of disabledpeople.